THU0615 Participants' experience of the making it work program, an online program to help people with inflammatory arthritis remain employed. (15th June 2017) - Li, A; Backman, C; As, B van; Rogers, P; Gignac, M; Li, L; Esdaile, J; Lacaille, D
Abstract : Objectives: Health services addressing employment needs for people with arthritis are lacking. To address this need, we developed the Making it Work (MiW) program, an online self-management program aimed at helping people with inflammatory arthritis (IA) deal with employment issues. As part of a randomized controlled trial evaluating program effectiveness, this study reports on participants' experiences with various aspects of the program. Methods: All participants in the MiW program between Jan20 and Dec7 2016 were included. Participants were recruited from rheumatologist practices, outpatient arthritis programs, a national consumer organization (Arthritis Consumer Experts), and community advertisements in BC, Alberta and Ontario. Eligibility criteria included: having IA; being currently employed; age 18–59 yrs; concern about their ability to work; and access to a computer. The program consisted of 5 online self-learning modules, 5 online group meetings facilitated by a vocational counsellor, an individual ergonomic assessment by an occupational therapist and an online session with a vocational counsellor. Feedback questionnaires were administered online after participants completed the program. Descriptive analyses were performed. Results: The sample included 69 participants [80% female; mean (SD) age: 45.3 (10.5) yrs; 83% Caucasian; 91% with post-secondary education; 52% with RA, AS: 19%, SLE: 17%; PsA: 12%]. Overall, participants expressed satisfaction with the program with 94.2% agreeing (69.6% strongly and 24.6% somewhat) they would recommend this program to someone they know. When asked to rate program components on a scale of 0–10 where 0=not useful at all and 10=very useful, participants rated all components favourably: median [25Q;75Q] for online modules: 8 [7;10], with highest ratings for the fatigue module (rated 10 by 42%); online group meetings: 9 [7.5;10]; ergonomic and VRC assessments: 8 [7;10] each. Although participants had 2 weeks between meetings to complete the module, 55% did the module the week of, and 42% the day before, the group meeting. Median time to complete each module was 60 min. 81% enjoyed being able to listen to the information (somewhat or strongly agreed), although 35% stated they would have preferred to read the information than listen to a narrator. 74% expect to use the online modules again in the future. Participants were also satisfied with the online group meetings: 93% were very or somewhat satisfied with the group facilitation; 87% satisfied with the group dynamic; 84% comfortable with the online format. When asked to rate their online group meeting experience on a scale of 1 to 10, median [25Q;75Q] ratings for: ability to follow group discussion was 10 [9;10]; getting to know other participants: 7 [7;10]; feeling listened to and understood 9 [8;10]; feeling that group was supportive 9 [7;10]. 20% said it was difficult for them to attend group meetings. Conclusions: In general, participants were highly satisfied with all aspects of the MiW program. Our study demonstrates that self-management programs, including group meetings, can be successfully delivered using an online format, which facilitates wider dissemination, with greater convenience to patients, and at lower costs. Disclosure of Interest: None declared